Experimental demonstration of a hyper-entangled ten-qubit Schrödinger cat state - Gao, Wei-Bo; Lu, Chao-Yang; Yao, Xing-Can; Xu, Ping; Gühne, Otfried; Goebel, Alexander Matthias; Chen, Yu-Ao; Peng, Cheng-Zhi; Chen, Zeng-Bing; Pan, Jian-Wei (Nature physics, 2010)
Creating entangled photon states becomes technologically ever more difficult as the number of particles increases, and the current record stands at six entangled photons. However, using both their polarization and momentum degrees of freedom, up to ten-qubit states can be encoded in ‘only’ five photons, as has now been demonstrated.